2019
DOI: 10.22630/pniks.2019.28.1.11
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on improve the functioning of extensive green roofs in city centers using mosses

Abstract: Most of environmental benefits of green roofs results from the presence of a vegetation layer. However vascular plants quickly die in harsh urban conditions. This paper presents research involving moss species appearing spontaneously on green roofs in cities to test whether we can create a vegetation layer with simplifi ed structure introducing that moss. It was checked using two transplant methods and three models of such roofs. Research evidenced that moss Ceratodon purpureus Hedw. is able to survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Cryptogams requiring little or no soil may be valuable and more affordable alternatives to conventional green-roof plantings (Grant, 2006). Compared with roofs colonised by vascular plants, moss roofs need less care, they can undergo multiple cycles of dehydration/rehydration without losing photosynthetic performance, and they can be thinner, which makes their installation easier (Anderson et al, 2010;Burszta-Adamiak et al, 2019;de Carvalho et al, 2020;Perini et al, 2020). Bryophytes are suitable as substitutes for vascular plants in green facade and roof systems, taking advantage of some of their characteristics, such as their ability to colonize different construction materials (Garabito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptogams requiring little or no soil may be valuable and more affordable alternatives to conventional green-roof plantings (Grant, 2006). Compared with roofs colonised by vascular plants, moss roofs need less care, they can undergo multiple cycles of dehydration/rehydration without losing photosynthetic performance, and they can be thinner, which makes their installation easier (Anderson et al, 2010;Burszta-Adamiak et al, 2019;de Carvalho et al, 2020;Perini et al, 2020). Bryophytes are suitable as substitutes for vascular plants in green facade and roof systems, taking advantage of some of their characteristics, such as their ability to colonize different construction materials (Garabito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Scandinavian countries vegetated green roofs were historically built with the aim to preserve a favourable indoor climate in the house as a moss-covered roof helps to avoid heat losses and hinders the penetration of water into the house (Emilsson, 2005). On the other hand, however, it is often suggested that a spontaneously formed moss cover on the roof should be removed (Burszta-Adamiak et al, 2019). A bryophyte cover may spare the roofing material as many bryophytes produce antibacterial and mould repellent compounds and hinder the spread of saprotrophic microorganisms (Asakawa, 1998;Hedderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They require minimal or no irrigation and are usually planted from moss, succulents, grasses and some herbaceous plants (Dunnett & Kingsbury, 2004;Oberndorfer et al, 2007;Burszta-Adamiak, Fudali, Łomotowski & Kolasińska, 2019). This type of green roofs is the most widely used and they can be installed on most roofs.…”
Section: Introductionmentioning
confidence: 99%